Pengaruh Efisiensi Supply Chain Terhadap Pencapaian Target Produksi dan Kinerja Perusahaan - Prakoso, Bagus Imam; Huda, Miftakul; Fauzianto , Irfan; Junaedi, Dodi; Sunandar, Legar (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the impact of supply chain management efficiency on achieving company performance and production targets. In the era of increasingly intense global competition, companies are required to optimize all aspects of their operations, especially in the effective and efficient management of their supply chains. The research method uses a quantitative approach with multiple regression analysis, involving a sample of 150 manufacturing companies. Data collection was conducted through structured questionnaires and direct observations of companies' supply chain processes. The variables studied include supply chain integration, partner coordination, inventory management, and supply chain information systems on production performance and the achievement of company targets.